DSwitch: a dual mode direct and network attached disk - Zhang, Quanlu; Dai, Yafei; Zhang, Lintao (Sixth ACM Symposium on Cloud Computing (SoCC), 2015)
Putting computers into low power mode (e.g., suspend-toRAM) could potentially save significant amount of power when the computers are not in use. Unfortunately, this is often infeasible in practice because data stored on the computers (i.e., directly attached disks, DAS) might need to be accessed by others. Separating storage from computation by attaching storage on the network (e.g., NAS and SAN) could potentially solve this problem, at the cost of lower performance, more network congestion, increased peak power consumption, and higher equipment cost. Though DAS doesnot suffer these problems, it is not flexible for power saving. In this paper, we present DSWITCH, an architecture that, depending on the workload, allows a disk to be attached either directly or through network. We design flexible workload migration based on DSWITCH, and show that a wide variety of applications in both data center and home/office settings can be well supported. The experiments demonstrate that our prototype DSWITCH achieves a power savings of 91.9% to 97.5% when a disk is in low power network attached mode, while incurring no performance degradation and minimal power overhead when it is in high performance directly attached mode.